The Use of Video in Teaching Speaking - Sufrisa Sufrisa; Arifin Syamaun; Diana Fauzia Sari (Research in English and Education Journal, 2019)
The research problem of this study that does the use of video in teaching speaking improve students’ speaking skill at the VIII4 Graders of SMPN 1 Peukan Bada Aceh Besar. The objective study is to find out the use of video in teaching speaking improve students’ speaking skill at the VIII4 Graders of SMPN 1 Peukan Bada Aceh Besar. It is focused on the use of video to improve students’ speaking ability, especially on vocabulary at the VIII4 Graders of SMPN 1 Peukan Bada. The method used was descriptive quantitative research. The population was the second year students of SMPN 1 Peukan Bada Aceh Besar. The sample was 19 students of class VIII4 by using purposive sampling. The data was pre-test and post-test. Based on the calculation of the data, it can be seen that there was significant difference between the result of pre test and post test. The mean of pre-test result was 67 and the post-test result was 76,47. In this case, the result of test indicated that the achievement of students in post test is higher than that of pre test. It means video can improve students’ speaking ability, especially at the VIII4 Graders of SMPN 1 Peukan Bada Aceh Besar.